Electrochemical Sensing of Vitamin C Using Graphene/Poly-Thionine Composite Film Modified Electrode - Murugan, Ridhu V.; Magesh, Vasanth; Vijayalakshmi, K.; Atchudan, Raji; Arya, Sandeep; Sundramoorthy, Ashok K. (Micro and Nanosystems, 2024)
Background: Gastric irritation and kidney problems occur due to excess ascorbic acid content, whereas the lack of ascorbic acid in the human body leads to poor wound healing, muscle degeneration, and anemia. Objectives: Herein, we report the development of an electrochemical sensor for the detection of ascorbic acid using poly-thionine/ graphene (P-Th/Gr) modified glassy carbon electrode (GCE) in 0.1 M phosphate buffer solution (PBS) (pH 7.4). Electrostatically fused graphene affixed with poly-thionine was successfully illustrated for effective voltammetric sensing of ascorbic acid. Methodology: FE-SEM indicated the blended edge of a 2D graphene sheet with a deposited thin layer of polymer, which confirmed the formation of a poly-thionine/graphene composite. The cyclic voltammetry (CV) technique was utilized for the electrochemical assay of ascorbic acid (AsA, Vitamin C). Results: With the increased concentrations of AsA, the oxidation peak current of ascorbic acid increased at 0.0 V, and the overpotential showed a decrease compared to bare GCE. The effect of scan rate on cyclic voltammograms was recorded with 500 μM of ascorbic acid from 10 mV/s to 250 mV/s, which indicated that AsA oxidation is a diffusion-controlled process on poly-thionine/ graphene-modified electrode. Conclusion: It was concluded that a poly-thionine/graphene composite-based sensor could be useful for the determination of ascorbic acid in various biological samples.
Keywords: sensor